Judiciary on Russian Constitutional System - Arkhipov, Vladislav (2013)
This article is about new constitutional order in Russia emphasizing fundamental areas as the role of judiciary in the Russian Constitutional System from 1993 Constitution, the one which replaced the 1978 Russian Soviet Federative Socialist Republic Constitution based on communist ideology. Therefore, it is intended to examine the principle of separation of powers, constitutionally recognized human rights and liberties, relationship between international bodies’ case law of human rights and the Russian Constitutional Court, among others issues.